Antenatal care practices for gestational weight gain: a cross sectional survey of antenatal care providers reported provision and barriers to providing recommended care - Jenna L. Hollis; Kristine Deroover; Justine Daly; Belinda Tully; Michelle Foster; Christophe Lecathelinais; Craig E. Pennell; John Wiggers; Melanie Kingsland (BMC, 2024)
Abstract Background Implementation of recommended gestational weight gain (GWG) care by antenatal care providers is poor. It is unclear whether practice implementation and barriers differ between antenatal care provider profession or experience. This study aimed to assesses the provision of and barriers to guideline care for GWG and examine associations with professional discipline and years of experience. Methods A cross sectional survey was conducted with antenatal care providers working in three public maternity services in a regional city in Australia. Data were collected on the provision of and barriers (informed by the Theoretical Domains Framework) to recommended GWG care. Data were summarised using descriptive statistics. Associations between health profession characteristics (professional discipline and years providing antenatal care) and GWG care practices and barrier outcomes were assessed using multivariate logistic regression. Results 117 antenatal care providers completed the survey (75% participation rate). One quarter (25%) reported that they routinely provided recommended GWG assessment at the first antenatal visit, and 9% at subsequent visits. Only 7% routinely provided recommended advice on GWG, healthy eating and physical activity. Professional discipline or years of experience were not associated with higher odds of GWG practices. Skills, belief about capabilities, belief about consequences and environmental context and resources were barriers to providing care. Medical professionals had higher odds of agreeing that they have been adequately trained to address GWG (OR = 9.14, 95%CI:3.10-26.90) and feel competent in having sensitive conversations with pregnant women about GWG (OR = 8.60, 95%CI:2.29-32.28) than midwives. Midwives had higher odds of agreeing that there are services they can refer pregnant women to for further support (OR = 2.80, 95%CI:1.13-6.91). Conclusions The provision of antenatal care for GWG was low, inconsistently provided and did not differ by professional discipline or years of experience. Antenatal care providers report numerous barriers including skills, belief about capabilities, belief about consequences, and environmental context and resources. Barriers to GWG care provision differed by professional discipline, but not years of providing care. The findings demonstrate that the type and prioritisation of practice-change implementation strategies may need to be tailored to address the differential barriers faced by professional groups.